CLINICAL FEATURES AND OUTCOMES OF INFANTS WITH RETINOPATHY OF PREMATURITY WHO FAIL ANTIVASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY. Issue 11 (November 2021) - Xu, Lucy T.; Levine, David A.; Hutchinson, Amy K.; Rao, Prethy; Hubbard, George B.
Abstract : Purpose: To describe characteristics and outcomes of patients with retinopathy of prematurity who failed intravitreal antivascular endothelial growth factor. Methods: A retrospective case series of 211 eyes (112 patients) treated with antivascular endothelial growth factor as initial therapy for retinopathy of prematurity at a single academic institution between 2011 and 2019 and an additional 6 eyes (3 patients) referred to us for management of failed antivascular endothelial growth factor. Results: Among the 211 eyes receiving initial treatment at our institution, 17 eyes (11%) failed. Of the 23 total eyes managed by us for failure, 3 eyes (13%) failed after 50-week postmenstrual age. Failure manifested as recurrent plus in 14 eyes (58%), recurrent Stage 3 in 13 eyes (54%) and retinal detachment in 5 eyes (21%). Treatment failures were managed with laser (13 eyes), repeat injection (4 eyes), vitrectomy (2 eyes), or a combination of modalities (4 eyes). Follow-up of ≥6 months was available for 18 of the 23 eyes. The retina was fully attached in 17 eyes, and fixation behavior was present in 10 eyes. Conclusion: The most common manifestations of treatment failure were recurrent plus and Stage 3. The failure rate at our institution was 11.0%. A significant proportion of failures occurred after 50-week postmenstrual age. Most failed eyes had favorable anatomical outcomes and over half demonstrated fixation behavior. Abstract : Failure after a single dose of antivascular endothelial growth factor for retinopathy of prematurity most commonly manifested as recurrent plus or recurrent Stage 3. Most patients with failure had favorable anatomical outcomes and half demonstrated fixation behavior.